The potential of universal basic income schemes to mitigate shocks: Comparing the performance of universal basic income in Uganda and Zambia during COVID-19 - Enrico Nichelatti; Maria Jouste; Pia Rattenhuber (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
The debate over universal basic income (UBI) has gained traction in the developing world in recent years. We analyse the effects of four UBI schemes on poverty and inequality measures during normal times and times of crisis in Uganda and Zambia. We use static microsimulation models and nationally representative household surveys for each country. Our results show that in Zambia, where the existing social protection benefits have more extensive coverage, the least generous UBI benefit leads to higher poverty and inequality compared to existing benefits. By contrast, in Uganda, a country with only one notable social protection programme, all UBI scenarios reduce poverty and inequality. Differences between welfare estimates for the existing systems and UBI scenarios whether in normal or crisis times are not large though when UBI policies are revenue neutral or expenditures calibrated to the regional average. In normal times and in times of crisis, poverty reduction increases with the generosity of the UBI benefit amount in both countries. UBI schemes clearly outperform existing systems only with UBI benefit amounts that result in unrealistic expenditure levels.
Keywords: D31; H55; I32; 330; universal basic income; COVID-19; microsimulation; poverty; inequality